Educational Perspectives on Indigenous Country Music:Review of Clinton Walker's Buried Country:The Story of Aboriginal Country Music (Annandale, NSW:Pluto Press, 2000) and associated multimedia resources - Ryan, Robin (The Australian Journal of Indigenous Education, 2001)
Songs are not divided from contemporary Aboriginal life; they just bleed out of it as a creative response to more than two centuries of powerlessness. Buried Country is a multimedia resource on Aboriginal 'country' music, an essential resource for educational and public libraries.